Before I fall in love - Lee, Coco; Sony Music Entertainment (Kuala Lumpur : Sony Music Entertainment, 1999)
Contains the single taken from the album Just No Other Way, also featured on The Runaway Bride Soundtrack.
CD 1 : Before I Fall In Love.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Popular music